The handbook of road safety measures - Elvik, Rune (Emerald, 2009)
The second edition of the "Handbook of Road Safety Measures" (previously published in 2004) gives state-of-the-art summaries of current knowledge regarding the effects of 128 road safety measures. It covers all areas of road safety including: traffic control; vehicle inspection; driver training; publicity campaigns; police enforcement; and, general policy instruments. With many original chapters revised and several new ones added, extra topics covered in this edition include: post-accident care; DUI legislation and enforcement; environmental zones; and speed cameras